Molecular genetic investigations for increasing the production results of farm animals - Árnyasi, Mariann (Acta Agraria Debreceniensis, 2001)
The author analysed the publications related to molecular genetics presented at the 51st annual meeting of the European Association for Animal Production. Her aim was to make the latest molecular genetic results known and to emphasise that this discipline plays an increasingly important role in research and the practical fields of animal breeding and production.